2011
DOI: 10.1007/s11060-011-0680-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of interstitial continuous vincristine infusion in a bioluminescent rodent intracranial tumor model

Abstract: Interstitial chemotherapeutic drug infusion can bypass the blood-brain barrier, and provide high regional drug concentrations without systemic exposure. However, toxicity and efficacy for drugs administered via interstitial continuous (i.c.) infusion have not been characterized. In the current study, vincristine (VIN) was infused into the right frontal lobes of healthy Fisher 344 rats at 30, 45, 60, and 120 μg/ml over a period of 7 days at 1 μl/h, using an Alzet osmotic pump to evaluate toxicity. C6 rat gliobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Based on previous work from our laboratory [5,30,31] and other studies [32][33][34][35], CED is an effective drug delivery method, allowing for 100% delivery of chemotherapeutic agents. It is a promising delivery method for large therapeutic agents such as monoclonal antibodies [36], antisense oligonucleotides [37], immunotoxins [38,39], or viral vectors [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous work from our laboratory [5,30,31] and other studies [32][33][34][35], CED is an effective drug delivery method, allowing for 100% delivery of chemotherapeutic agents. It is a promising delivery method for large therapeutic agents such as monoclonal antibodies [36], antisense oligonucleotides [37], immunotoxins [38,39], or viral vectors [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] CED can bypass the BBB to deliver therapeutic agents to the brain tumors; reduce systemic drug levels to minimize side effects; and provide prolonged elevation of intracerebral chemotherapeutic agents relative to systemic administration. 13,14 Our laboratory 15,16 and others [17][18][19][20][21] have confirmed that CED is an effective delivery method for brain tumor treatment. However, even with this delivery method, sustained localized distribution and prolonged retention after drug delivery remain major challenges.…”
Section: Introductionmentioning
confidence: 82%
“…16 To evaluate the therapeutic effects of treatment, 5 μl of 0.9% saline, NDs(5 mg/ml), DOX(1 mg/ml) or ND(5 mg/ml)-Dox(1 mg/ ml) were administered via CED, 7 days after tumor inoculation into Fisher 344 rats, or 14 days after inoculation into NIH-RNU nude rats. The luciferase substrate, D-luciferin (150 mg of luciferin/kg of body weight), was injected intraperitoneally 10 min before direct visualization using IVIS Xenogen Imaging System.…”
Section: Therapeutic Efficacy In An Orthotopic Glioma Xenograft Rodenmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested the efficacy after interstitial treatment with various chemotherapy agents including carboplatin. Dr. Guifa Xi, who succeeded this research project in my lab, treated them with vincristine, and the results of efficacy and toxicity were published in 2011 [57]. For that study, first, vincristine toxicities after direct injection to the brain stem in a rat were tested to optimize the dosage [58].…”
Section: Brainstem Tumorsmentioning
confidence: 99%